2018
DOI: 10.1097/iae.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Angiography of Pachychoroid Pigment Epitheliopathy

Abstract: Pachychoroid pigment epitheliopathy is forme fruste of CSC. There is no difference between complicated and UCP regarding subfoveal choroidal thickness and choroidal vessel density. The main difference between these groups is choroidal hyperpermeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…Choroidal hyperpermeability is believed to result from increased extravasation of fluid and lipoprotein-bound ICGA from the choriocapillaris or the larger choroidal vessels into the surrounding choroidal stroma. Previous studies have reported choroidal hyperpermeability to be present in >90% of eyes with PPE and CSC [27], and in 10-50% of eyes with PCV [2,18]. Punctate hyperfluorescence spots have also been observed in the mid to late phase of ICGA in eyes with CSC and PCV [18,31].…”
Section: Choroidal Vascular Hyperpermeabilitymentioning
confidence: 90%
See 3 more Smart Citations
“…Choroidal hyperpermeability is believed to result from increased extravasation of fluid and lipoprotein-bound ICGA from the choriocapillaris or the larger choroidal vessels into the surrounding choroidal stroma. Previous studies have reported choroidal hyperpermeability to be present in >90% of eyes with PPE and CSC [27], and in 10-50% of eyes with PCV [2,18]. Punctate hyperfluorescence spots have also been observed in the mid to late phase of ICGA in eyes with CSC and PCV [18,31].…”
Section: Choroidal Vascular Hyperpermeabilitymentioning
confidence: 90%
“…Punctate hyperfluorescence spots have also been observed in the mid to late phase of ICGA in eyes with CSC and PCV [18,31]. Both diffuse and punctate hyperfluorescent spots have been frequently observed in contralateral eyes of patients with CSC and PCV without overt pathology [27,30]. These ICGA findings characteristically persist in eyes with CSC even after resolution of SRF [30].…”
Section: Choroidal Vascular Hyperpermeabilitymentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, pigmentary changes in a leopard-spot pattern characteristic of UES were not identified in our patients; 2) ICGA in our patients was very characteristic for PDS and included typical findings such as dilated large choroidal veins (pachyvessels) and choroidal hyperpermeability. 1,4,12,13 The pachyvessels were identified during dye transit and washed out in the late phase of the study. These pachyvessels corresponded to dilated Haller layer vessels visible on structural EDI-OCT and typically illustrated attenuation of the overlying Sattler layer and choriocapillaris.…”
Section: Discussionmentioning
confidence: 99%